PHOTODETACHMENT OF THE NEGATIVE IODINE ION INCLUDING RELAXATION EFFECTS - (:unkn) unknown (AMER PHYSICAL SOC, 1992)
The effects of relaxation on the photodetachment of the iodine negative ion are calculated using the recently developed relativistic random-phase approximation with relaxation. In this method the outgoing electron is calculated in the field of the relaxed negative ion with one electron removed (i.e., in the field of the atom). Overlap integrals between orbitals of the initial and final states are included. It is found that the relaxation effects for the negative iodine atom are significantly larger than those for the corresponding neutral atom Xe. Comparison is made with results calculated by the relativistic random-phase approximation and with experiment near the 5p threshold.
Keywords: RANDOM-PHASE APPROXIMATION; PHOTO-IONIZATION; PHOTOIONIZATION; SUBSHELLS; BA